Biodiversity patterns diverge along geographic temperature gradients - Charlie J. G. Loewen; Donald A. Jackson; Benjamin Gilbert (Global Change Biology, 2023)
Models applying space‐for‐time substitution, including those projecting ecological responses to climate change, generally assume an elevational and latitudinal equivalence that is rarely tested. However, a mismatch may lead to different capacities for providing climatic refuge to dispersing species. We compiled community data on zooplankton, ectothermic animals that form the consumer basis of most aquatic food webs, from over 1200 mountain lakes and ponds across western North America to assess biodiversity along geographic temperature gradients spanning nearly 3750 m elevation and 30° latitude. Species richness, phylogenetic relationships, and functional diversity all showed contrasting responses across gradients, with richness metrics plateauing at low elevations but exhibiting intermediate latitudinal maxima. The nonmonotonic/hump‐shaped diversity trends with latitude emerged from geographic interactions, including weaker latitudinal relationships at higher elevations (i.e. in alpine lakes) linked to different underlying drivers. Here, divergent patterns of phylogenetic and functional trait dispersion indicate shifting roles of environmental filters and limiting similarity in the assembly of communities with increasing elevation and latitude. We further tested whether gradients showed common responses to warmer temperatures and found that mean annual (but not seasonal) temperatures predicted elevational richness patterns but failed to capture consistent trends with latitude, meaning that predictions of how climate change will influence diversity also differ between gradients. Contrasting responses to elevation‐ and latitude‐driven warming suggest different limits on climatic refugia and likely greater barriers to northward range expansion.

Altered frontal-mediated inhibition and white matter connectivity in pediatric chronic tic disorders - Adrienne B. Bruce; Weihong Yuan; Donald L. Gilbert; Paul S. Horn; Hannah S. Jackson; David A. Huddleston; Steve W. Wu (Experimental Brain Research, 2021)

Climate warming moderates the impacts of introduced sportfish on multiple dimensions of prey biodiversity - Charlie J. G. Loewen; Angela L. Strecker; Benjamin Gilbert; Donald A. Jackson (Global Change Biology, 2020)
Human‐assisted introductions of exotic species are a leading cause of anthropogenic change in biodiversity; however, context dependencies and interactions with co‐occurring stressors impede our ability to predict their ecological impacts. The legacy of historical sportfish stocking in mountainous regions of western North America creates a unique, natural quasiexperiment to investigate factors moderating invasion impacts on native communities across broad geographic and environmental gradients. Here we synthesize fish stocking records and zooplankton relative abundance for 685 mountain lakes and ponds in the Cascade and Canadian Rocky Mountain Ranges, to reveal the effects of predatory sportfish introduction on multiple taxonomic, functional and phylogenetic dimensions of prey biodiversity. We demonstrate an innovative analytical approach, combining exploratory random forest machine learning with confirmatory multigroup analysis using multivariate partial least‐squares structural equation models, to generate and test hypotheses concerning environmental moderation of stocking impacts. We discovered distinct effects of stocking across different dimensions of diversity, including negligible (nonsignificant) impacts on local taxonomic richness (i.e. alpha diversity) and trophic structure, in contrast to significant declines in compositional uniqueness (i.e. beta diversity) and body size. Furthermore, we found that stocking impacts were moderated by cross‐scale interactions with climate and climate‐related land‐cover variables (e.g. factors linked to treeline position and glaciers). Interactions with physical morphometric and lithological factors were generally of lesser importance, though catchment slope and habitat size constraints were relevant in certain dimensions. Finally, applying space‐for‐time substitution, a strong antagonistic (i.e. dampening) interaction between sportfish predation and warmer temperatures suggests redundancy of their size‐selective effects, meaning that warming will lessen the consequences of introductions in the future and stocked lakes may be less impacted by subsequent warming. While both stressors drive biotic homogenization, our results have important implications for fisheries managers weighing the costs/benefits of stocking—or removing established non‐native populations—under a rapidly changing climate.

Early transcriptional response pathways in Daphnia magna are coordinated in networks of crustacean‐specific genes - Luisa Orsini; James B. Brown; Omid Shams Solari; Dong Li; Shan He; Ram Podicheti; Marcus H. Stoiber; Katina I. Spanier; Donald Gilbert; Mieke Jansen; Douglas B. Rusch; Michael E. Pfrender; et al. (Molecular Ecology, 2018)
Natural habitats are exposed to an increasing number of environmental stressors that cause important ecological consequences. However, the multifarious nature of environmental change, the strength and the relative timing of each stressor largely limit our understanding of biological responses to environmental change. In particular, early response to unpredictable environmental change, critical to survival and fitness in later life stages, is largely uncharacterized. Here, we characterize the early transcriptional response of the keystone species Daphnia magna to twelve environmental perturbations, including biotic and abiotic stressors. We first perform a differential expression analysis aimed at identifying differential regulation of individual genes in response to stress. This preliminary analysis revealed that a few individual genes were responsive to environmental perturbations and they were modulated in a stressor and genotype‐specific manner. Given the limited number of differentially regulated genes, we were unable to identify pathways involved in stress response. Hence, to gain a better understanding of the genetic and functional foundation of tolerance to multiple environmental stressors, we leveraged the correlative nature of networks and performed a weighted gene co‐expression network analysis. We discovered that approximately one‐third of the Daphnia genes, enriched for metabolism, cell signalling and general stress response, drives transcriptional early response to environmental stress and it is shared among genetic backgrounds. This initial response is followed by a genotype‐ and/or condition‐specific transcriptional response with a strong genotype‐by‐environment interaction. Intriguingly, genotype‐ and condition‐specific transcriptional response is found in genes not conserved beyond crustaceans, suggesting niche‐specific adaptation.

Dynamic recruitment of amino acid transporters to the insect/symbiont interface - Rebecca P. Duncan; Filip Husnik; James T. Van Leuven; Donald G. Gilbert; Liliana M. Dávalos; John P. McCutcheon; Alex C. C. Wilson (Molecular Ecology, 2014)
Symbiosis is well known to influence bacterial symbiont genome evolution and has recently been shown to shape eukaryotic host genomes. Intriguing patterns of host genome evolution, including remarkable numbers of gene duplications, have been observed in the pea aphid, a sap‐feeding insect that relies on a bacterial endosymbiont for amino acid provisioning. Previously, we proposed that gene duplication has been important for the evolution of symbiosis based on aphid‐specific gene duplication in amino acid transporters ( AAT s), with some paralogs highly expressed in the cells housing symbionts (bacteriocytes). Here, we use a comparative approach to test the role of gene duplication in enabling recruitment of AAT s to bacteriocytes. Using genomic and transcriptomic data, we annotate AAT s from sap‐feeding and non sap‐feeding insects and find that, like aphids, AAT gene families have undergone independent large‐scale gene duplications in three of four additional sap‐feeding insects. RNA ‐seq differential expression data indicate that, like aphids, the sap‐feeding citrus mealybug possesses several lineage‐specific bacteriocyte‐enriched paralogs. Further, differential expression data combined with quantitative PCR support independent evolution of bacteriocyte enrichment in sap‐feeding insect AAT s. Although these data indicate that gene duplication is not necessary to initiate host/symbiont amino acid exchange, they support a role for gene duplication in enabling AAT s to mediate novel host/symbiont interactions broadly in the sap‐feeding suborder Sternorrhyncha. In combination with recent studies on other symbiotic systems, gene duplication is emerging as a general pattern in host genome evolution.

Lemming winter habitat choice: a snow-fencing experiment - Donald G. Reid; Frédéric Bilodeau; Charles J. Krebs; Gilles Gauthier; Alice J. Kenney; B. Scott Gilbert; Maria C.-Y. Leung; David Duchesne; Elizabeth Hofer (Oecologia, 2012)

Reliability of maximal muscle force and voluntary activation as markers of exercise-induced muscle damage - James Peter Morton; Greg Atkinson; Donald PM MacLaren; Nigel Tim Cable; Gareth Gilbert; Caroline Broome; Anne McArdle; Barry Drust (European Journal of Applied Physiology, 2005)

Estimating the density and biomass of moray eels (Muraenidae) using a modified visual census method for hole-dwelling reef fauna - Marianne Gilbert; Joseph B. Rasmussen; Donald L. Kramer (Environmental Biology of Fishes, 2005)

Paleoenvironmental assessment from the physical properties of lacustrine and marine sediments: a Canadian contribution to IGCP 374 - Robert Gilbert; Joseph R. Desloges; Donald S. Lemmen (Journal of Paleolimnology, 1997)

Toxicologic studies with japanese quail fed winter wheat grown on municipal sludge-amended soil - Gilbert S. Stoewsand; John N. Telford; Judy L. Anderson; Carl A. Bache; Walter H. Gutenmann; Donald J. Lisk (Archives of Environmental Contamination and Toxicology, 1984)

Safety evaluation of vegetables cultured on municipal sewage sludge-amended soil - Juanell N. Boyd; Gilbert S. Stoewsand; John G. Babish; John N. Telford; Donald J. Lisk (Archives of Environmental Contamination and Toxicology, 1982)

Nutritional and toxicological studies with growing pigs fed aquatic plant rations - Tuan N. Yap; Wilson G. Pond; Jung F. Wu; Gilbert S. Stoewsand; Patricia C. Wszolek; Donald J. Lisk (Archives of Environmental Contamination and Toxicology, 1979)